Cold Atmospheric Plasma Enhances TGF-β1, CTGF Protein Expression, and Healing in Full-Thickness Skin Burns: An Animal Study - Sahar M. Gebril; Fakhr El din M. Lasheen; Mohamed Khalaf; Amr Abdelhamed; Manal I. Bahkali; Fayez El Hossary; Mahmoud Rezk Abdelwahed Hussein (Biomolecules, 2025)
Cold atmospheric plasma (CAP) interacts with tissues, leading to fast wound disinfection. Given the frequent global burden of burn injuries and the risks of infection associated with acute full-thickness burns (FTBs), this investigation examined CAP as a potential therapeutic method for wound healing due to its antimicrobial and pro-healing effects. Here, we examined the impacts of CAP on the healing of wounds resulting from acute FTSBs. We established an animal model that included four groups: (1) healthy control animals without burns, (2) untreated animals with acute FTSBs, (3) animals with acute FTSBs treated with CAP for 5 s per day for 21 days, and (4) animals with acute FTSBs treated with CAP for 10 s per day for 21 days. Wound healing was assessed using immunohistological methods. In animals with FTSBs, CAP therapy was accompanied by (i) accelerated wound closure, (ii) enhanced regeneration of the dermis and epidermis, and (iii) increased protein expression of transforming growth factor-β1 (TGF-β1) and connective tissue growth factor (CTGF). These changes were more pronounced following CAP treatment for 10 s per day compared to CAP treatment for 5 s per day.